Comparison of visual acuity in reduced lumination and facility of ocular accomodation in table tennis champions and non-players - Jafarzadehpur, E.; Yarigholi, M. R. (Journal of Sports Science & Medicine, 2004)
A table tennis player should fixate at different distances; track the objects with different speed, and in different visual environment. Their visual skills must be well developed for these capabilities. Therefore, visual acuity in reduced lumination and facility of ocular accommodation those are two criteria for visual skills have been compared in table tennis players and normal non-players. Twenty-nine young table tennis champions and 29 normal matched non-players (did not take part in any racket sports game) were evaluated. Basic visual and eye examinations were done for both of them. Normal results in basic examination were fundamental requirement for all the subjects. +/-2.00 sphere lenses for accommodation facility are used. An electrical current regulator changed the output light intensity of a conventional chart projector (Topcon). Light intensity decreased to 10 cd·m-2 and visual acuity tested. In comparison of visual acuity in reduced lumination and facility of ocular accommodation in table tennis champions and non-players there are significant differences (p < 0.001). In the preliminary visual tests there was not any significant different in the two groups but the results in the top level table tennis player was very uniform and in every test and the standard deviation was lesser in tennis player group than non-players. These results show that motor and sensorial functions of expert players are well developed. That is consistent with other researchers. This result was interpreted as reflecting a better perceptual system of experts to the constraints encountered during table tennis and its use in practical settings for evaluating athletes or detecting sport talents. However some visual and perceptual training that usually used in orthoptics can be used for novice table tennis player to improve their abilities.